Prognostic impact of incomplete hematologic count recovery and minimal residual disease on outcome in adult acute lymphoblastic leukemia at the time of second complete response. Issue 2 (1st February 2018) - Saygin, Caner; Papadantonakis, Nikolaos; Cassaday, Ryan D.; Liedtke, Michaela; Fischer, Katrina; Dunn, Tamara; Patel, Bhumika J.; Sobecks, Ronald; Kalaycio, Matt; Sekeres, Mikkael A.; Mukherjee, Sudipto; Gerds, Aaron T.; et al.
Abstract: Outcomes of relapsed adult acute lymphoblastic leukemia (ALL) have improved over time with the introduction of new therapies as well as better supportive care. However, there is still a need for easy-to-use and accurate prognostic tools for patients in first relapse. Whether complete response (CR) with incomplete count recovery (CRh) can be grouped with CR in relapsed ALL trials has not been formally studied. We analyzed 106 ALL patients at first relapse who were treated at three academic centers and achieved CR/CRh. White blood cell count at initial diagnosis and receiving hematopoietic cell transplant (HCT) were independent predictors of overall survival after relapse, while minimal residual disease (MRD) positivity and performance of HCT were predictors of relapse free survival (RFS). Patients who achieved MRD negativity and underwent HCT had the best outcomes. Our results suggest that MRD is a more powerful predictor of outcome than CRh.